2023
DOI: 10.1007/s11227-023-05073-x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the class imbalance problem in network intrusion detection systems using data resampling and deep learning

Abstract: Network intrusion detection systems (NIDS) are the most common tool used to detect malicious attacks on a network. They help prevent the ever-increasing different attacks and provide better security for the network. NIDS are classified into signature-based and anomaly-based detection. The most common type of NIDS is the anomaly-based NIDS which is based on machine learning models and is able to detect attacks with high accuracy. However, in recent years, NIDS has achieved even better results in detecting alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…The writers of [33] also recommended a CNN in order to reach 93.2%. In order to attain an accuracy of 87.25, the authors in [34] recommended use a CNN. This work addresses the issue of class imbalance by presenting a number of deep learning models and a data resampling method based on the tomek links and ADASYN algorithms.…”
mentioning
confidence: 99%
“…The writers of [33] also recommended a CNN in order to reach 93.2%. In order to attain an accuracy of 87.25, the authors in [34] recommended use a CNN. This work addresses the issue of class imbalance by presenting a number of deep learning models and a data resampling method based on the tomek links and ADASYN algorithms.…”
mentioning
confidence: 99%
“…The investigation proposed in [37] extends the analysis using other techniques such as adaptive synthetic (ADASYN), Tomek-Link (T-Link), and T-Link with ADASYN combined with DL models, such as MLP, CNN, and a combination between a CNN and a particular type of recurrent neural network (RNN), that is, a BiLSTM. Furthermore, the evaluation of sampling techniques is extended, considering the combination between random undersampling (RUS) and random oversampling (ROS).…”
Section: Handle Class Imbalance In Web Phishing Classificationmentioning
confidence: 74%
“…D. Musleh et al [18] innovatively applied feature extraction techniques using VGG-16 and DenseNet on intrusion datasets and, through the employment of ML models such as Random Forest, K-Nearest Neighbors, and Support Vector Machine (SVM), achieved an accuracy of 92.40%. Other notable IDSs, including those developed by G. Logeswari et al [19], J. O. Mebawondu et al [20], and A. Abdelkhalek et al [21], have reported accuracies of 82.20%, 76.96%, and 83.50%, respectively. Moreover, the Secured Automatic Two-level Intrusion Detection System (SATIDS) introduced by A. R. Elsayed et al [22] showcases a remarkable accuracy of 96.56%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notably, G. Logeswari et al[19], and J. O. Mebawondu et al[20] presented systems with significantly lower overall performance metrics, highlighting the advanced capabilities of Deep-IDS in handling various intrusion types effectively. A. R. Elsayed et al[21] and P. Kumar et al[23] also proposed systems with high accuracy rates of 96.56% and 97.45%, respectively, but neither matched the balanced performance across all metrics achieved by Deep-IDS. This comparison underscores the robustness and efficiency of Deep-IDS in…”
mentioning
confidence: 99%